“Military Shura Council” The Military Regime in the Arabian Kingdom of Syria For the Year 1919 : Historical Study - "Al-Asima" Newspaper as a Source - Aljawarneh أحمد; Alomari عمر (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study aims to identify the aspirations of prince Faisal Bin Hussein in building a force for the Syrian Arab Army. After returning from attending the Versailles Conference in Paris on 28 June 1919, Prince Faisal sensed the importance of establishing an organized and newly trained army to protect the gains of the Syrian Arab state. In order for this project to achieve the hoped-for success, and its desired objectives, he assigned General Allenby, commander-in-chief of the Egyptian and Arab army in Syria, to do this task, he agreed to do so, and thus, the “Military Shura Court", headed by Major General "Yassin Al-Hashemi", was established. Al-Asimah newspaper was the first to launch a comprehensive review of the structure of the Military Divan. This newspaper also revealed the the bases and system of recruitment, volunteering, salaries and military clothing, as well as the privileges of soldiers and a supplement to the Law of Enlistment.